2011
DOI: 10.1586/eri.11.137
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes: infection beyond the skin

Abstract: Propionibacterium acnes is a Gram-positive bacterium that forms part of the normal flora of the skin, oral cavity, large intestine, the conjunctiva and the external ear canal. Although primarily recognized for its role in acne, P. acnes is an opportunistic pathogen, causing a range of postoperative and device-related infections. These include infections of the bones and joints, mouth, eye and brain. Device-related infections include those of joint prostheses, shunts and prosthetic heart valves. P. acnes may pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
164
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(179 citation statements)
references
References 101 publications
(116 reference statements)
2
164
0
3
Order By: Relevance
“…This result is consistent with previous observations in the shoulder 10,40,45,46 and in the spine 41 . Propionibacterium usually did not grow on culture of dermal specimens from female subjects whereas dermal cultures were commonly positive for male patients.…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with previous observations in the shoulder 10,40,45,46 and in the spine 41 . Propionibacterium usually did not grow on culture of dermal specimens from female subjects whereas dermal cultures were commonly positive for male patients.…”
Section: Discussionsupporting
confidence: 94%
“…Overall, the genus Propionibacterium was the most abundant OTU (22.2%). These are Gram-positive rod-shaped bacteria with probiotic properties in humans, although some species are opportunistic pathogens [51,52]. Another study found that the three dominant bacterial phyla were Tenericutes (44.2%), Proteobacteria (39.22%) and Firmicutes (13.09%), and the genus Spiroplasma was the most abundant OTU (44.1%) [48].…”
Section: Microbial Contaminationmentioning
confidence: 99%
“…(epidermidis, caprae, capitis, or hominis) had, on average, remarkably low sMAC levels (~8 ng/ml). These organisms are frequent opportunistic pathogens, particularly on medical devices such as prosthetic heart valves, joint prostheses, and shunts (50)(51)(52)(53)(54). However, given that the organisms grew out in broth only or from later shunt taps, it is possible that these patients did not have true meningitic shunt infections.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%